Tannin and Saponin Contents of Different Organs of Melastoma Malabathricum L. as a Preliminary Basis for Methane-Mitigation Research in Ruminants - Roni Pazla; Antonius; Erpomen; Yolani Utami; Zaitul Ikhlas; Gusri Yanti; Aslizah Mohd-Aris; Ahmad Sanusi; Fitri Wadeviola; Fatimah Aini; Rizki Romadhon; Mega Novianti; Hijratul Alkharizi; Bintang Farras (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Melastoma (M) malabathricum L. is a phytochemically rich tropical plant with potential relevance to methane-mitigation research in ruminants. This study aimed to characterize the tannin and saponin contents of different organs of M. malabathricum L. as a preliminary basis for evaluating its prospective use as a phytogenic resource for livestock. Samples were collected from Padang Pariaman Regency, West Sumatra, Indonesia, and separated into roots, stems, leaves, flowers, and fruits for analysis. Tannin content was analyzed using the hide powder method based on the Folin-Ciocalteu reaction, while saponin content was determined using the TLC scanner method. The results showed clear variations in both metabolites among plant organs. Flowers had the highest tannin content, whereas the roots had the highest saponin content. These findings indicate an organ-specific distribution of bioactive compounds in M. melabathricum L. and suggest that this plant may serve as a promising botanical resource for further studies on methane mitigation. However, as the present study was limited to phytochemical characterization, further in vitro and in vivo studies are required to verify the effects of this extract on rumen fermentation and methane production.